1994
DOI: 10.1182/blood.v83.3.822.822
|View full text |Cite
|
Sign up to set email alerts
|

A novel deletion of approximately 27 kb including the beta-globin gene and the locus control region 3'HS-1 regulatory sequence: beta zero- thalassemia or hereditary persistence of fetal hemoglobin?

Abstract: A novel deletion of approximately 27 kb with the 5′ breakpoint 1.5 to 2.2 kb upstream of the beta-globin gene, and the 3′ breakpoint approximately 24 kb downstream of the beta-globin gene, has been found in five members of two families from Southeast Asia (Vietnam and Cambodia). Six members of another family from China, previously reported from our laboratory, have also been shown to carry this deletion. The patients presented with mild hypochromia and microcytosis, a hemoglobin (Hb) A2 level of approximately … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
1

Year Published

1999
1999
2002
2002

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 37 publications
2
12
0
1
Order By: Relevance
“…Patients were from Guangdong Province and Hunan Province of mainland China. Of them, two unrelated adult carriers with high Hb F levels (22.2% and 29.1%, respectively) were detected when screened for ␤-thalassemia [14] and were further identified by DNA analysis as patients with deletional HPFH, which was of the same type as previously described in individuals of Southeast Asia [12,13]. The DNA samples from the two patients were used to characterize the breakpoints of this defect and to construct a PCR-based diagnosis method.…”
Section: Methodsmentioning
confidence: 94%
See 3 more Smart Citations
“…Patients were from Guangdong Province and Hunan Province of mainland China. Of them, two unrelated adult carriers with high Hb F levels (22.2% and 29.1%, respectively) were detected when screened for ␤-thalassemia [14] and were further identified by DNA analysis as patients with deletional HPFH, which was of the same type as previously described in individuals of Southeast Asia [12,13]. The DNA samples from the two patients were used to characterize the breakpoints of this defect and to construct a PCR-based diagnosis method.…”
Section: Methodsmentioning
confidence: 94%
“…Preliminary testing showed that the proband bore a deletional chromosome inherited from her mother leading to HPFH [12,13] in addition to a 14-15 (+G) frameshift. To get more evidence, family study was carried out by typing the HPFH deletion and by analyzing parameters of red blood cells and composition of Hbs in all the members in three generations of the family from the matrilineal line.…”
Section: Family Study and Prenatal Diagnosismentioning
confidence: 99%
See 2 more Smart Citations
“…It was also found that types of mutation are ethnic specific [8]. Three different mutations have been previously described in Vietnamese individuals including the 4-bp deletion at codons 41/42, a 27-kb deletion including the ␤-globin gene and the HS-1 site of LCR, and the novel frameshift mutation at codon 95 (+A) [9][10][11]. The first screening for ␤-thalassemia in Vietnam was performed in the North of Vietnam, situated between China in the north and Laos in the northwest [12].…”
Section: Introductionmentioning
confidence: 99%